2005
DOI: 10.1103/physrevlett.94.065503
|View full text |Cite
|
Sign up to set email alerts
|

Photoexcitation of a Volume Plasmon inC60Ions

Abstract: Neutral C60 is well known to exhibit a giant resonance in its photon absorption spectrum near 20 eV. This is associated with a surface plasmon, where delocalized electrons oscillate as a whole relative to the ionic cage. Absolute photoionization cross-section measurements for C+60, C2+60, and C3+60 ions in the 17-75 eV energy range show an additional resonance near 40 eV. Time-dependent density functional calculations confirm the collective nature of this feature, which is characterized as a dipole-excited vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
182
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(214 citation statements)
references
References 28 publications
29
182
3
Order By: Relevance
“…Scully et al, were reported in [10]. The authors associated the lower peak near 20 eV with a surface plasmon, its frequency being 3 times smaller than the Langmuir frequency [2].…”
Section: Collective Dipole Oscillation Of Delocalized Electrons In a mentioning
confidence: 93%
See 2 more Smart Citations
“…Scully et al, were reported in [10]. The authors associated the lower peak near 20 eV with a surface plasmon, its frequency being 3 times smaller than the Langmuir frequency [2].…”
Section: Collective Dipole Oscillation Of Delocalized Electrons In a mentioning
confidence: 93%
“…The authors associated the lower peak near 20 eV with a surface plasmon, its frequency being 3 times smaller than the Langmuir frequency [2]. The other peak (about 40 eV) is associated by the authors with some volume plasmon of unknown origin [10].…”
Section: Collective Dipole Oscillation Of Delocalized Electrons In a mentioning
confidence: 99%
See 1 more Smart Citation
“…For a different variety of spectral minima, which are abundant in the photoemission of cluster systems, TDLDA has probed attosecond structures in the emission delay [26]. Other successes of TDLDA include the capture of the full landscape of electronic collective motions in C 60 driven by photon that produce experimentally detected plasmon resonances [27,28]. Very recently, TDLDA has predicted attosecond time delays of the valence photoionizations of C 60 at the giant plasmon resonance that showed negative delay behavior over a range of the resonance, matching the outcome of a simple semiclassical modeling [29].…”
Section: Introductionmentioning
confidence: 99%
“…The jellium model is employed for computing the relative delay [35]. This model enjoyed earlier successes in codiscovering with experimentalists a high-energy plasmon resonance [36], interpreting the energy-dependent oscillations in C 60 valence photo-intensities [37], and predicting giant enhancements in the confined atom's photoresponse from the coupling with C 60 plasmons [19]. Significant ground state hybridization of Ar 3p is found to occur with the C 60 3p orbital, resulting in 3p[Ar+C 60 ] and 3p[Ar-C 60 ] from, respectively, the symmetric and antisymmetric wavefunction mixing.…”
mentioning
confidence: 99%